Impact of liposomal amphotericin B therapy on chronic pulmonary aspergillosis. Issue 5 (November 2016) - Newton, Pippa J.; Harris, Chris; Morris, Julie; Denning, David W.
Summary: Objectives: To assess the clinical response and renal toxicity observed in chronic pulmonary aspergillosis (CPA) patients receiving ≥1 short-courses of liposomal amphotericin (LAmB) (AmBisome ® ) therapy. Methods: A retrospective audit of clinical response and renal function was undertaken in 71 CPA patients (41 male) treated with LAmB at the National Aspergillosis Centre, including 20 patients receiving repeated treatment courses or long-term therapy (n = 5). Results: Median age was 64 years (range 29–86 years). Treatment indications included respiratory symptoms (n = 33; 46.5%), constitutional symptoms (n = 2; 2.8%) or both (n = 36; 50.7%). 48 patients (73.8%) responded to their first LAmB course. Quality of life (QOL) improvements occurred in 37 (92.5%) of 40 patients with sufficient data available. Response rates for repeated short-courses of LAmB were 76.6%; QOL improvements were observed in 91.7% of treatment courses. All patients on long-term therapy demonstrated a response. 34 (50%) and 17 (25%) patients respectively developed an increased risk of acute kidney injury (AKI) or actual AKI with their first treatment; a significant reduction in geometric mean eGFR was observed and a similar pattern occurred following their second treatment course. Conclusions: Whilst CPA is responsive to LAmB, caution should be exercised with repeated courses, if other treatments are available. Highlights: Clinical response to the first LAmB course in CPA patients was 74%. Improvements in QOL in CPA patients after their first LAmB course was 92%. 50% of CPA patients had an increased risk of AKI with their first LAmB course. 25% of CPA patients developed AKI with their first LAmB course. The geometric mean eGFR in CPA patients was reduced post LAmB therapy.